Evolving policy: Malaysian diplomacy in the South China Sea - Yew Meng Lai; Cheng-Chwee Kuik (Australian Institute, 2021)
Malaysia has pragmatically optimised diplomatic and legal instruments as the principal forms of statecraft to advance its interests. Diplomacy and selective deference are central to preserving sovereignty and keeping bilateral ties, while legal means have served to protect Malaysia’s interests through quiet, indirect defiance. These instruments, used together, have enabled Malaysia, a smaller and militarily weaker state, to deepen its light-hedging, while pursuing oil and gas exploration activities in its claimed areas (quiet developmental actions). Light hedging is essentially a non-confrontational, low profile, and seemingly contradictory approach through which a weaker state hopes to defend its maritime-territorial integrity and safeguard economic interests while offsetting multiple risks in an increasingly uncertain external environment.